Since \(y\) depends on \(x\) and \(x\) depends on \(t\text{,}\) it follows that we can also think of \(y\) depending directly on \(t\text{.}\) We can use substitution and the notation of functions to determine this relationship.
First, it’s important to realize what the rule for \(f\) tells us. In words, \(f\) says “to generate the output that corresponds to an input, take the input and square it, and then subtract \(1\text{.}\)” In symbols, we might express \(f\) more generally by writing “\(f(\Box) = \Box^2 - 1\text{.}\)”
Now, observing that \(y = f(x) = x^2 - 1\) and that \(x = g(t) = 3t - 4\text{,}\) we can substitute the expression \(g(t)\) for \(x\) in \(f\text{.}\) Doing so,
\begin{align*}
y &= f(x)\\
&= f(g(t))\\
&= f(3t-4)\text{.}
\end{align*}
Applying the process defined by the function \(f\) to the input \(3t-4\text{,}\) we see that
\begin{equation*}
y = (3t-4)^2 - 1\text{,}
\end{equation*}
which defines \(y\) as a function of \(t\text{.}\)